Hydroxyl radical scavenging activity of titanium oxide nanocrystals - Maksimchuk, P.; Hubenko, K.; Seminko, V.; Onishchenko, A.; Bespalova, I.; Onishchenko, A.; Prokopiuk, V.; Tkachenko, A.; Yefimova, S. (My University, 2022)
The efficiency of reactive oxygen species scavenging by titanium oxide nanocrystals in water solutions is close to that of nanoceria (CeO2-x nanocrystals) of the same size suggesting that titanium oxide nanoparticles can be effective as an antioxidant in living cells as well. Moreover high biocompatibility of synthesized nanocrystals could be associated with their reactive oxygen species scavenging ability, which make them a prospective material for biomedical applications.
Keywords: titanium oxide nanocrystals; Hydroxyl radical scavenging